Staying hot to fight the heat-high body temperatures accompany a diurnal endothermic lifestyle in the tropics - Levesque, D; Tuen, Andrew A.; Lovegrove, B.G. (Springer-Verlag GmbH Germany, 2018)
Much of our knowledge of the thermoregulation of endotherms has been obtained from species inhabiting cold and temperate climates, our knowledge of the thermoregulatory physiology of tropical endotherms is scarce. We studied the thermoregulatory physiology of a small, tropical mammal, the large treeshrew (Tupaia tana, Order Scandentia) by recording the body temperatures of free-ranging individuals, and by measuring the resting metabolic rates of wild individuals held temporarily in captivity. The amplitude of daily body temperature (~4 °C) was higher in treeshrews than in many homeothermic eutherian mammals; a consequence of high active-phase body temperatures (~40 °C), and relatively low rest-phase body temperatures (~36 °C). We hypothesized that high body temperatures enable T. tana to maintain a suitable gradient between ambient and body temperature to allow for passive heat dissipation, important in high-humidity environments where opportunities for evaporative cooling are rare. Whether this thermoregulatory phenotype is unique to Scandentians, or whether other warm climate diurnal small mammals share similar thermoregulatory characteristics, is currently unknown.